Synthesis and electrochemical, electrochromic and electrical properties of novel s-triazine bridged trinuclear Zn(II), Cu(II) and Lu(III) and a tris double-decker Lu(III) phthalocyanines - ÖZKAYA, ALİ RIZA; DUMLUDAĞ, FATİH (ELSEVIER SCIENCE SA, 2011)
The new s-triazine-bridged trinuclear Zn(II) and Cu(II) phthalocyanines have been synthesized from the reaction of corresponding anhydrous metal salts, Zn(OAc)(2) and CuCl with 4,5-bis(hexylthio)-phthalonitrile and 2,4,6-tris(2-thiophthalonitrile)-s-triazine. The tris phthalonitrile derivative of s-triazine was prepared from the reaction of 4-nitrophthalonitrile and thiocyanuric acid in dry dimethylformamide as solvent using K2CO3 as the base. The same route was applied to prepare the trinuclear Lu(III) phthalocyanine analogue. The conversion of tris phthalonitrile into its isoindoline derivative was accomplished by bubbling ammonia gas through a solution in methanol in the presence of sodium methoxide. The cyclization of two different isoindoline derivatives and 4,5-bis(hexylhthio)-1,2-diiminoisoindoline, with lutetium (III) acetate in dimethylformamide gave trinuclear Lu(III) phthalocyanine. The reaction of this complex with octakis-hexylthio phthalocyanine led to the isolation of tris double-decker Lu(III) phthalocyanine. The structures of the target compounds were confirmed by elemental analysis, UV-vis, IR and MALDI-TOF mass spectroscopies. The d.c. and a.c. conductivities of the phthalocyanine compounds were measured as a function of temperature. The small value of pre-exponential factor suggested the conduction by localized states in the band tails and by localized states near the Fermi level. The temperature dependence of the frequency exponent showed that the conduction in these compounds is due to hopping of charge carriers. The tris double-decker phthalocyanine complex showed well-defined electrochromic behaviour with green-blue and blue-purple colour transitions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Trinuclear phthalocyanines; Tris double-decker; A.c. conductivity; Impedance spectra; Electrochemistry; Electrochromism; LANGMUIR-BLODGETT-FILMS; SENSING PROPERTIES; LUTETIUM(III) PHTHALOCYANINE; AC CONDUCTIVITY; DIPHTHALOCYANINE; CHALCOGENIDE; DEPENDENCE; BEHAVIOR; LU2PC4